Diagnostic and Treatment Challenges of Paroxysmal Nocturnal Hemoglobinuria in Uganda. (31st January 2019) - Lumori, Boniface Amanee Elias; Muyanja, Daniel
Abstract : Introduction . Paroxysmal nocturnal hemoglobinuria (PNH) is a very rare disorder of the hematopoietic stem cells which is often underdiagnosed. Its incidence is about 5 cases per million inhabitants in a year, and currently, there are only 1610 patients in the International PNH Registry. In this report, we describe a case of PNH in southwestern Uganda. Case Presentation. A 34-year-old man, subsistence farmer, with a history of multiple prior presentations with anemia, jaundice, and dark-colored urine requiring blood transfusions presented to us again in July 2018 with a week's history of palpitations, dizziness, and dark-colored urine. Investigations done suggested a direct antiglobulin test- (DAT-) negative hemolytic anemia, and subsequently, flow cytometry showed a large clone of PNH. He received many blood transfusions and hematinics on several occasions during the course of his admissions. Conclusions . Our report showed diagnostic and treatment challenges of PNH in health resource-limited setting.